Directive 2010/64/EU of the European Parliament and of the Council on the Right to Interpretation and Translation in Criminal Proceedings: Transposition Strategies with regard to Interpretation and Translation - Hertog, Erik (MonTi Monografías de Traducción e Interpretación, 2016)
It is difficult to overestimate the importance of Directive 2010/64/EU on the right to interpretation and translation in criminal proceedings. It is the first directive under the Lisbon Treaty, the first directive in the field of Justice (up till then one had recourse to framework decisions only), the first directive on language since the founding treaties of the EU and, of course, the first directive on issues of translation and interpretation. In this contribution we will discuss the relevant policy-making history leading up to the Directive, highlight the main challenges the Directive presents to the Member States that need to transpose this binding Directive into their own legislation and practice and, finally, suggest a number of strategies and policies that could help the transposition process, both in the short and long term.